2019
DOI: 10.1002/cld.845
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Care for Cystic Fibrosis Liver Disease: Where Does the Adult Hepatologist Fit In?

Abstract: http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/14-5-reading-ayoub a video presentation of this article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Cystic Fibrosis (CF) is one of the most common inherited genetic disorder in Caucasians. A mutation in Cystic Fibrosis Transmembrane Conductance Regulator (CTFR) gene is the cause of the disease [1]. The CTFR gene encodes for the chloride ion channel, belonging to adenosine triphosphate's family.…”
Section: Introductionmentioning
confidence: 99%
“…Cystic Fibrosis (CF) is one of the most common inherited genetic disorder in Caucasians. A mutation in Cystic Fibrosis Transmembrane Conductance Regulator (CTFR) gene is the cause of the disease [1]. The CTFR gene encodes for the chloride ion channel, belonging to adenosine triphosphate's family.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that multidisciplinary clinics improve outcomes [10] , [11] , [12] , reduce mortality [13] , [14] , and are a cost-effective approach to patient care [4] , [5] . However, limited studies were identified which assess the utilization and efficacy of automatic referrals in a multidisciplinary CF clinic [15] .…”
Section: Introductionmentioning
confidence: 99%